Financial fragility of the banking system in emerging economies: Mexican case - Bernuy Barrera, Marcial Orlando (2022)
Objective: To describe the determinants of banking system fragility in emerging economies, fundamentally limited to the Mexican banking system. Method: The research was descriptive, based on quantitative information of the Mexican banking system in order to show the behavior of relevant financial indicators associated with the financial fragility of banking systems in emerging economies. Results: The banking systems in emerging economies show levels of financial fragility, generated by the incidence of critical economic-financial events registered at the international level, and observed in the relevant financial indicators of liquidity, solvency, soundness and profitability. Conclusions: The behavior of relevant macroeconomic and financial variables, along with insufficient levels of liquidity and global capital or solvency within the context of a scenario with predominance of financial risks, show the level of fragility of the Mexican banking system.